Dietary Patterns in Colombia: An Exploratory and Confirmatory Factor Analysis - Meneses Urrea, Luz Adriana; Vaquero Abellán, Manuel; Benachi Sandoval, Narly; Villegas Arenas, Dolly; Osorio Murillo, Olga; Molina-Recio, Guillermo (Frontiers in Food Science and Technology, 2022)
This study aimed to construct and validate dietary patterns in Colombian individuals aged between 15 and 64 years. The study sample consisted of 16,216 individuals who participated in the 2015 National Survey on the Nutritional Situation of Colombia (ENSIN). To identify dietary patterns, an exploratory analysis was first conducted with 16 food groups with 70% of the study sample, followed by a confirmatory analysis with the remaining 30%. Four eating patterns were identified, referred to as traditional, industrialized, conservative, and grilled foods/drinks. The traditional pattern presented the highest variance (17.65%), followed by the industrialized (14.36%), conservative (10.74%), and grilled foods/drinks (7.57%) patterns. Regarding the frequency of food consumption, the preference for the consumption of rice/pasta and panela/sugar/honey was evident. In contrast, low consumption of whole foods, energizers, light foods, supplements, and salt was observed. The dietary patterns in Colombia continue to be characterized by a high consumption of panela/sugar/honey and low consumption of fruits/vegetables, which is why the development of public health interventions to improve these habits, such as health promotion and chronic disease prevention tools, is considered necessary.